Media starter system for improve student learning outcomes - Suyitno; Hartanto, Pulung Dwi; Purnawan; Kurniawan, Arif; Nurtanto, Muhammad; Mutohhari, Farid (AIP conference proceedings, 2023)
This study aims to find out the procedure for developing starter system learning media as a learning tool for improving student learning outcomes, measure how appropriate the learning media is for improving student learning outcomes, measure student learning outcomes after using starter system learning media. The type of research used is Research and development (R&D) to produce products and test products in improving student learning outcomes. The research subjects were 50 students. Data collection techniques in this study used tests, questionnaires, and documentation. The data obtained are the results of the evaluation, student responses about the media, validation, and reliability. The results of the assessment by media experts get a percentage of 97.50% in the very good category, the material expert assessment gets a percentage score of 92.5% in the very valid category. Student responses went through two stages, namely the limited group trial of the media getting a score percentage of 92.25% in the very good category and the media response taken from the experimental class which was the subject of the application of the media to get an average value (mean) of 83.2, so that the information obtained by 17 students was stated passed and 8 students were declared to have not passed because the score was still less than the KKM, so it could be concluded by looking at the results of the media assessment, the media was in the very good category.